The analysis of polysemous words In HSK level 1 exam papers - Cheng, Ching Yee; Yong, Ying Mei (2016)
The Hanyu Shuping Kaoshi (HSK, Chinese Proficiency Test) Level 1 has set 150 vocabulary list as test syllabus. This vocabulary list has controlled the quantity of vocabulary to ensure the selection of vocabulary is suitable for the beginner learners. However, the HSK Level 1 vocabulary list did not provide the reference to select the part of speech categories and the senses of meaning. These issues such as mislabel of the part of speech categories and the unknown of the senses of meaning will cause teaching problems for Chinese teachers and misunderstanding for HSK test takers. Thus this paper aims to analyze the polysemous words that occurred in 26 set of HSK Level exam papers. The analysis will focus on two issues such as the part of speech categories and the senses of meaning. The result showed that the polysemous words phenomena caused issues in the part of speech and the meaning transform. This paper will provide some suggestions to improve the HSK Level vocabulary list and teaching reference for Chinese teachers based on the result.